Composite resin composition, fiber-reinforced composite material, and method for producing same
Hydrophobic nanocellulose fibers dispersed in a monomer to form a thermoplastic epoxy resin address uniform dispersion issues, resulting in a composite material with high rigidity, low gravity, and improved mechanical properties.
Patent Information
- Application Number
- JP2020092921
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-28
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2040-05-28
AI Technical Summary
Existing composite materials face challenges in uniformly dispersing nanocellulose fibers in resins due to differences in polarity and viscosity, leading to agglomeration, reduced impact strength, and increased specific gravity, which complicates secondary processing and affects mechanical properties.
Hydrophobic nanocellulose fibers with specific thickness and surface modifications are dispersed in a monomer, which is then polymerized to form a thermoplastic epoxy resin, ensuring uniform dispersion and improved mechanical properties.
The resulting composite resin composition exhibits high rigidity, low specific gravity, excellent molded appearance, and thermal stability, with enhanced mechanical properties such as increased bending, impact, and interlaminar shear strength.
Smart Images

Figure 0007620269000001 
Figure 0007620269000002 
Figure 0007620269000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite resin composition and a fiber-reinforced composite material which are excellent in environmental characteristics due to the use of biomass materials, and which have a low specific gravity, high rigidity and excellent molded appearance, and a method for producing the same. [Background technology]
[0002] In recent years, biomass materials have been attracting attention from the perspective of environmental protection, and composite materials with naturally derived organic fillers and biopolymers have begun to be used as materials for the automotive, OA, and electrical and electronic fields. In addition, methods of blending inorganic fillers such as glass fibers into resin compositions have been investigated for the purpose of improving mechanical strength such as rigidity and heat resistance. However, these inorganic fillers need to be added in large quantities, which increases the specific gravity of the molded product and also increases the amount of residue that becomes waste when incinerated or disposed of, placing a burden on the environment.
[0003] Patent Document 1 discloses a technique for compounding an aromatic polycarbonate resin with an aliphatic polyester and a naturally derived organic filler to obtain a resin composition having excellent mechanical properties and flame retardancy, using jute fiber or rayon fiber as a naturally derived organic filler. However, the resin composition obtained in Patent Document 1 has a large decrease in impact strength, an insufficient molded appearance, is highly colored, and has insufficient thermal stability during molding.
[0004] Patent Document 2 discloses a polycarbonate resin composition containing 100 parts by mass of a resin mixture consisting of (A) 99-60% by mass of polycarbonate resin and (B) 1-40% by mass of cellulose fibers having an average fiber diameter of 5-50 μm and an average fiber length of 0.03-1.5 mm, and (C) 0.2-30 parts by mass of a terpene compound, the resin composition being excellent in environmental characteristics due to the use of biomass materials, low specific gravity, high rigidity, excellent molded appearance, good thermal stability, and flame retardancy. However, although this resin composition is said to have a low specific gravity, its specific gravity (g / cm3) exceeds 1.20 in all examples, which is larger than the specific gravity of water and does not fully address the issue of reducing the weight of the constituent materials.
[0005] Patent Document 3 discloses a composition production technique that includes cellulose and a dispersant, the dispersant having a resin affinity segment A and a cellulose affinity segment B, and a block copolymer structure or a gradient copolymer structure, but when an olefin resin is combined, a maleic anhydride modified resin is used in combination, and the resin cannot be dispersed alone, and many aggregates of 10 μm or more are present. Furthermore, although the elastic modulus is improved at the strength level, the impact strength is significantly reduced.
[0006] Patent Document 4 discloses a technique for producing a hydrophilic nanofiber composite material, which is characterized by solvating the hydroxyl groups of hydrophilic nanofibers having hydroxyl groups with a hydrophilic organic solvent and mixing the solvated hydroxyl groups with a molten plastic.
[0007] Patent Document 5 discloses a dispersion in which both nanocellulose fibers and a resin are dispersed in a dispersion medium, as well as a resin composition containing nanocellulose fibers in a resin.
[0008] Patent Document 6 discloses a sheet-like molded product at least partially using a polyamide resin composition in which cellulose fibers having a small average fiber diameter are well dispersed without agglomeration in the polyamide resin, and the sheet-like molded product has excellent tearability, small thermal shrinkage, and excellent thermal dimensional stability. The sheet-like molded product is molded using a polyamide resin composition containing 0.1 to 10 parts by mass of cellulose fibers per 100 parts by mass of polyamide resin, and the average fiber diameter of the cellulose fibers in the sheet-like molded product is 10 μm or less. The sheet-like molded product is obtained by carrying out a polymerization reaction of monomers constituting the polyamide resin in the presence of cellulose fibers containing water.
[0009] Patent Document 7 discloses a carbon fiber reinforced plastic having improved fatigue life by incorporating cellulose nanofibers with an optimal fiber length, and a carbon fiber reinforced plastic to which cellulose nanofibers with an average fiber length of 20 to 80 μm have been added in order to achieve the objective of providing a carbon fiber reinforced plastic having improved fatigue life and a manufacturing method thereof.
[0010] Patent Document 8 discloses a carbon fiber reinforced plastic in which 50 to 250 parts by mass of carbon fiber are blended with 100 parts by mass of a resin composition in which 0.05 to 1 mass % of cellulose nanofibers having an average fiber length of 0.05 μm to 100 μm are blended with a matrix resin in order to achieve the objective of providing a carbon fiber reinforced plastic with an improved bending fatigue life. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2010-215791 A [Patent Document 2] WO / 2013 / 133228 [Patent Document 3] Patent Publication 2014-162880 [Patent Document 4] Patent Publication No. 2013-170241 [Patent Document 5] Patent Publication No. 2013-166818 [Patent Document 6] JP 2016-14117 A [Patent Document 7] JP 2019-210434 A [Patent Document 8] JP 2019-1872 A Summary of the Invention [Problem to be solved by the invention]
[0012] As disclosed in Patent Document 4 and Patent Document 5, when nanocellulose fibers and resin are composited, melt kneading is usually used to melt and mix the resin. Patent Document 4 discloses a technique of preparing a methanol-substituted nanocellulose dispersion by removing water from the nanocellulose dispersion by solvent replacement with methanol, and adding this to a molten resin and mixing it. In particular, when hydrophilic nanocellulose is added to a molten resin in a solvent-dispersed state, a technique of using a resin with increased polarity is disclosed, since it cannot be mixed uniformly due to the difference in polarity. However, when a nanocellulose dispersion is added to a resin melt above the boiling point of the solvent, it is known that the nanocellulose aggregates and dries while forming a hydrogen bond, and even if the visual appearance is good, it is impossible to uniformly disperse at the nano level. Furthermore, Patent Document 5 discloses a technique for selecting a surfactant to improve the compatibility of nanocellulose with a highly polar powder resin, but even if it is uniformly mixed in an aqueous dispersion, nanocellulose cannot penetrate and disperse inside the powder solid resin, so the dispersion level cannot be below the powder particle size level. For example, if the size of the powder particles is 17 μm, the uniform dispersion level is limited to a size above that. Furthermore, regardless of which technology is used, the melt viscosity of the resin when it is thermally melted is generally high, and since the viscosity of the nanocellulose fiber dispersion is significantly different from the resin melt viscosity, in order to uniformly disperse the nanocellulose fibers, it is necessary to lower the melt viscosity of the resin to the same level as the nanocellulose fiber dispersion. However, in order to lower the melt viscosity of the resin, it is necessary to increase the resin temperature, but nanocellulose fibers, especially the hemicellulose component, begin to discolor and decompose at temperatures above approximately 200°C, so the resin temperature cannot be increased in order to prevent this. As a result, when combining nanocellulose fibers with resin, it was difficult to uniformly disperse the nanocellulose fibers in the resin.
[0013] The sheet-like molded product disclosed in Patent Document 6 has a problem in that ε-caprolactam, which is a polyamide monomer, is a resin that is easily deactivated by moisture and is also difficult to mix with cellulose fibers.
[0014] In addition, the carbon fiber reinforced plastics disclosed in Patent Documents 7 and 8 are made by adding cellulose nanofibers to CFRP using thermosetting resin to improve durability, but there are certain limitations to the mixing characteristics with the resin, and because they are thermosetting, secondary processing is difficult.
[0015] In view of the problems in the conventional technology described above, the present invention aims to provide a composite resin composition and a fiber-reinforced composite material that utilize biomass materials and have excellent environmental characteristics, as well as a low specific gravity, high rigidity, and excellent molded appearance, and a manufacturing method thereof.
[0016] As a result of extensive research, the inventors of the present invention have found that since the melt viscosity of the monomer is significantly lower than the melt viscosity of the polymer, and since hydrophobic nanocellulose fibers are easily dispersed in the monomer, when the hydrophobic nanocellulose fibers obtained by defibrating polysaccharides with a high-pressure water flow are added to the monomer and stirred, the hydrophobic nanocellulose fibers are uniformly dispersed in the monomer, and when the monomer is polymerized in such a state that the hydrophobic nanocellulose fibers are uniformly dispersed in the monomer, nanocellulose fibers with the hydrophobic nanocellulose fibers uniformly dispersed therein can be obtained. composite resin composition Furthermore, it has been found that the above-mentioned problems can be solved by obtaining the above-mentioned. Furthermore, it has been found that, since problems such as poor impregnation and the generation of voids occur due to the viscosity being too high during the impregnation into the reinforcing fibers, and thus the strength of the fiber-reinforced composite material decreases, by adjusting the degree of polymerization in the polymerization reaction, the resin composition can be satisfactorily impregnated into the reinforcing fibers. [Means for solving the problem]
[0017] That is, the present invention relates to the following composite resin composition. 1. A composite resin composition characterized by being obtained by polymerizing a mixture consisting of (A) 0.3 to 5 mass% hydrophobic nanocellulose fibers having an average thickness of 3 to 200 nm, a raw material α-cellulose content of 60% to 99 mass%, and in which some of the hydroxyl groups on the fiber surface have been substituted with hydrophobic functional groups, and (B) 99.7 to 95 mass% monomers that polymerize into a thermoplastic epoxy resin through a reaction. In the present invention, the term "resin" does not necessarily mean only a polymer, but also comprehensively refers to a monomer, a polymer, or a mixture of a monomer and a polymer.
[0018] 2. A fiber-reinforced composite material comprising the composite resin composition according to 1 above and reinforcing fibers.
[0019] 3. A fiber-reinforced composite material according to item 2, characterized in that the reinforcing fiber is a carbon fiber.
[0020] The present invention further relates to a method for producing the composite resin composition described below. 4. A method for producing a fiber-reinforced composite material, comprising the steps of: (A) impregnating reinforcing fibers with a mixture consisting of 0.3 to 5 mass% hydrophobic nanocellulose fibers having an average thickness of 3 to 200 nm, a raw material α-cellulose content of 60% to 99 mass%, and in which some of the hydroxyl groups on the fiber surface have been replaced with hydrophobic functional groups; and (B) 99.7 to 95 mass% epoxy-based monomers that polymerize through a reaction to become a thermoplastic epoxy resin; and polymerizing the monomers. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a conceptual diagram of a production apparatus for nanocellulose fibers, which are component (A) of the composite resin composition of the present invention. [Diagram 2] FIG. 2 is a conceptual diagram of another example of a production apparatus for nanocellulose fibers, which are the component (A) of the composite resin composition of the present invention. [Diagram 3] 1A and 1B are explanatory diagrams of an example of a reinforcing fiber fabric used in the present invention, in which (a) shows a state in which a resin is attached to the surface and inside of the reinforcing fiber fabric, and (b) shows a state in which a resin is not attached to the surface or inside of the reinforcing fiber fabric. [Figure 4] Diagram of the melt viscosity of monomers [Diagram 5] Schematic diagram of one embodiment of the present invention. [Figure 6] Schematic of the Example Process [Figure 7] Electron microscope enlarged photograph of the carbon fiber reinforced composite material obtained in the example [Figure 8] FIG. 1 is an explanatory diagram of a bending test method performed on the carbon fiber reinforced composite material obtained in the examples. [Figure 9] Graph showing the results of bending tests performed on carbon fiber reinforced composite materials obtained in the examples. [Figure 10] FIG. 1 is an explanatory diagram of the impact resistance test method performed on the carbon fiber reinforced composite material obtained in the examples. [Figure 11] Graph showing the results of impact resistance tests performed on carbon fiber reinforced composite materials obtained in the examples. [Figure 12] FIG. 1 is an explanatory diagram of a method for testing the apparent interlaminar shear strength by a short beam test performed on the carbon fiber reinforced composite material obtained in the examples. [Figure 13] Graph showing the results of apparent interlaminar shear strength tests by short beam tests performed on carbon fiber reinforced composite materials obtained in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] [(A) Hydrophobic nanocellulose fiber] Hydrophobicity refers to the property of a substance or molecule (or part of a substance) having a low affinity for water, i.e., being poorly soluble or miscible in water. Nanocellulose fibers have many hydroxyl groups in their molecules and are known to be extremely hydrophilic. Therefore, they undergo self-aggregation in a hydrophobic environment or in a dry state. As a result, it is not easy to mix them with highly hydrophobic resins, and conventional composites made by kneading nanocellulose fibers with polypropylene (PP) or polyethylene (PE) have not been able to exhibit the expected mechanical strength properties. Therefore, a method for sufficiently dispersing nanocellulose fibers in a hydrophobic environment was required.
[0023] Generally, when hydrophobic substituents are introduced into nanocellulose fibers to impart hydrophobicity, the reaction is carried out in a non-aqueous solvent. However, in the case of nanocellulose fibers, the hydroxyl groups present on the fibers' high specific surface area make them extremely hydrophilic. Therefore, it is difficult to remove water from nanocellulose fibers, and complicated procedures are required, such as multiple solvent replacements, dehydration treatments by overheating, or nano-ization in an organic solvent followed by a replacement reaction. In contrast, in the present invention, for example, hydrophobic cellulose nanofibers produced by the method for producing surface-hydrophobized cellulose nanofibers disclosed in WO2018 / 194080 can be used. However, as long as the cellulose nanofibers are hydrophobic, they are not particularly limited to this. Specifically, hydrophobic cellulose nanofibers used in the present invention can be obtained by dispersing cellulose nanofibers in a water-containing state in an organic solvent at a stirrable concentration, adding potassium carbonate in the range of 1 to 40 wt%, then adding vinyl esters and / or organic acid vinyl esters, reacting the mixture at a reaction temperature of 25°C to 100°C, and recovering the product after the reaction is completed. In this method, some of the hydroxyl groups in the cellobiose units of the cellulose nanofibers are replaced with vinyl esters, and hydrophobic cellulose nanofibers with a degree of substitution of 0.2 to 3.0 can be obtained. From the viewpoint of achieving both hydrophobicity and cellulose crystallinity, the degree of substitution is preferably 0.2 to 1.2.
[0024] [Nanocellulose fiber] In the present invention, by using hydrophobic nanocellulose fibers having a specific average thickness and dispersing without agglomeration as a biomass material, the cohesiveness of cellulose is suppressed, and the decrease in impact strength can be suppressed. Furthermore, since the (A) hydrophobic nanocellulose fibers can improve rigidity while having a low specific gravity compared to inorganic fibers such as glass fibers, a resin composition with high rigidity and low specific gravity can be obtained. As the nanocellulose fibers, for example, cellulose derived from woody plants and herbaceous plants can be used. Specific examples include nanocellulose fibers derived from polysaccharides containing natural plants such as wood fibers, bamboo fibers, sugarcane fibers, seed hair fibers, and leaf fibers. Furthermore, cellulose derived from sea squirts, which are marine components, and acetic acid bacteria can also be used. These nanocellulose fibers may be used alone or in combination of two or more types. In addition, pulp with an α-cellulose content of 60% to 99% by mass is used as the polysaccharide. If the purity is 60% by mass or more of α-cellulose, the fiber diameter and fiber length can be easily adjusted, and entanglement of the fibers can be suppressed. Compared with the case where an α-cellulose content is less than 60% by mass, the thermal stability during melting is high, there is no decrease in strength, and the coloring suppression effect is good, so that the effect of the present invention can be improved. Furthermore, if an α-cellulose content of more than 99% by mass is used, it becomes difficult to defibrate the fibers to the nano level. However, although cellulose derived from acetic acid bacteria is characterized by very high crystallinity, it is relatively easy to disentangle it into nanofibers.
[0025] The nanocellulose fibers in the present invention have an average diameter of 3 to 200 nm and are produced by defibrating polysaccharides with a high-pressure water stream. The average thickness was measured using a field emission scanning electron microscope JSM-7001FTTLS manufactured by JEOL Ltd. and a scanning probe microscope SPM-9700HT manufactured by Shimadzu Corporation. By defibrating the fibers to an average thickness of 3 to 200 nm, it is possible to obtain a resin composition that has flowability, little loss in impact strength, low specific gravity, high rigidity, and excellent molded appearance. If the average thickness is less than 3 nm, the degree of crystallinity decreases, which is undesirable from the standpoint of strength reinforcing ability. If the average diameter exceeds 200 nm, many fibers having a diameter of several tens of micrometers that have not been defibrated will be included, which is undesirable because it significantly reduces the fluidity and deteriorates the dispersibility. Defibration of polysaccharides with a high-pressure water stream can be carried out by colliding high-pressure water of about 50 to 400 MPa against a 0.5 to 10 mass % water mixture of polysaccharides.
[0026] One method for fibrillating this polysaccharide into nanocellulose fibers using a high-pressure water stream is the underwater counter-impingement method described in JP 2005-270891. This is a method in which natural cellulose fibers suspended in water are introduced into two opposing nozzles (Fig. 1: 108a, 108b) in a chamber (Fig. 1: 107), and are sprayed toward a single point from these nozzles, causing them to collide (Fig. 1). With this method, a suspension of natural microcrystalline cellulose fibers (e.g., Funacel) is collided in counter-impingement fashion, which nanofibrillates the surface and peels it off, improving the affinity with the carrier water, ultimately bringing the fibers to a state close to dissolution. The device shown in Figure 1 is a liquid circulation type, and is equipped with a tank (Figure 1: 109), a plunger (Figure 1: 110), two opposing nozzles (Figure 1: 108a, 108b), and a heat exchanger (Figure 1: 111) if necessary. Fine particles dispersed in water are introduced into the two nozzles, and are sprayed under high pressure from the opposing nozzles (Figure 1: 108a, 108b), causing counter-collision in the water. This method uses only water in addition to natural cellulose fibers, and nano-fine cellulose is obtained by only breaking down the interactions between the fibers, so there is no change in the structure of the cellulose molecules, and it is possible to obtain nanocellulose fibers with minimal reduction in the degree of polymerization due to breaking down.
[0027] Another method for fibrillating polysaccharides with a high-pressure water flow to produce nanocellulose fibers is the homogenization method described in JP 2012-36518 A, in which a dispersion liquid in which raw fibers are dispersed in a solvent is treated with a homogenizer equipped with a crushing-type homogenizing valve sheet. As shown in FIG. 2, according to this homogenization method, raw fibers 101, which are pumped through a homogenizer at high pressure, collide with the wall surface of the small-diameter orifice 102 (particularly the wall surface of the impact ring 103) when passing through a small-diameter orifice 102, which is a narrow gap, and are split by shear stress or cutting action, resulting in microfibrillation with a uniform fiber diameter. Nanocellulose fibers can also be produced by any suitable conventional method. Other known methods include a method of chemically modifying the cellulose surface using a TEMPO catalyst and then fibrillating it, a method of producing it by grinding it in a stone mill, and a method of finely pulverizing it with enzymes such as cellulase. Pellicles secreted by acetic acid bacteria are also a type of nanocellulose fiber, and can be used as they are or after mechanical fibrillation.
[0028] (A) Hydrophobic nanocellulose fibers having an average thickness of 3 to 200 nm, a raw material α-cellulose content of 60% to 99% by mass, and a part of the hydroxyl groups on the fiber surface substituted with hydrophobic functional groups. 1 (B) 99.7% by mass of a monomer that becomes a thermoplastic epoxy resin by polymerization through a reaction 99 In the mixture consisting of 0.3% by mass of component (A), the content of each component is 0.3 to 0.5% by mass of component (B). 1 Mass% and (B) component 99.7~ 99 Quantity %.
[0029] In the present invention, the term "resin" comprehensively refers to a monomer state, a polymer state, and a mixture of a monomer and a polymer state. [(B) Monomer that becomes a thermoplastic epoxy resin when polymerized by reaction] The monomer (B) of the present invention is the main component of the composite resin composition of the present invention, which exerts properties such as mechanical properties, moldability, solvent resistance, and heat resistance of the resin molded article obtained by polymerization.
[0030] Such a monomer is a monomer that becomes a thermoplastic epoxy resin. Specifically, a mixture of (a) a difunctional epoxy compound, (b) a difunctional phenol compound, and (c) a catalyst can be mentioned. (a) As the bifunctional epoxy compound, any bifunctional epoxy compound having two epoxy groups in the molecule can be used without particular limitation. From the standpoints of storage stability, tack-free property, thermoplasticity, and the mechanical properties of the resulting composite resin composition and fiber-reinforced composite material, bisphenol-type epoxy compounds, oligomer mixtures obtained by partial condensation of these (bisphenol-type epoxy resins), and dihydroxynaphthalene diglycidyl ether are preferred, and bisphenol-type epoxy resins are particularly preferred due to their low viscosity. (ii) As the bifunctional phenol compound, any compound having two phenolic hydroxyl groups in the molecule can be used without any particular limitation. However, catechol, resorcinol, hydroquinone, bisphenols, and mixtures thereof are preferred because they have a good balance of properties such as viscosity and adhesion to nanocellulose fibers and reinforcing fibers. The catalyst (c) is not particularly limited as long as it can promote the polymerization reaction between the components (a) and (b) and reduce crosslinking to such an extent that the epoxy resin obtained by polymerization has thermoplastic properties. Furthermore, it is preferable that the catalyst has the characteristic of preferentially promoting linear polymerization during polymerization. Specifically, examples of the catalyst include phosphorus-based catalysts, which preferentially catalyze the addition reaction between phenolic hydroxyl groups and epoxy groups rather than the anionic polymerization of epoxy groups, and imidazole-based catalysts having a substituent that suppresses nucleophilicity. The thermoplastic epoxy resin obtained by polymerizing the mixed system has the same molecular structure as phenoxy resin. By polymerizing the mixed system, the following advantages can be obtained: desirable properties such as thermoplasticity and mechanical properties of phenoxy resin, ease of dispersion of nanocellulose fibers due to the low viscosity of the monomer, and ease of handling in subsequent processes such as impregnation of reinforcing fibers due to the ability to control the degree of polymerization and adjust the viscosity by heating conditions, etc. [Polymerization] The polymer obtained by polymerizing the mixture consisting of 99.7 to 95 mass % of the (B) monomer of the present invention is the main component of the composite resin composition of the present invention, which expresses properties such as mechanical properties, molding processability, solvent resistance, and heat resistance of a resin molded product obtained by molding the composite resin composition of the present invention.
[0031] Furthermore, the mixture consisting of 99.7 to 95 mass % of the monomer (B) may contain rubbers such as those exemplified below. Specific examples of such rubbers include ethylene-propylene-non-conjugated diene copolymer rubber, ethylene-butene-1 copolymer rubber, ethylene-hexene copolymer rubber, ethylene-octene copolymer rubber, polybutadiene, styrene-butadiene block copolymer rubber, styrene-butadiene copolymer rubber, partially hydrogenated styrene-butadiene-styrene block copolymer rubber, styrene-isoprene block copolymer rubber, partially hydrogenated styrene-isoprene block copolymer rubber, polyurethane rubber, styrene graft-ethylene-propylene-non-conjugated diene copolymer rubber, styrene-graft-ethylene-propylene copolymer rubber, styrene / acrylonitrile-graft-ethylene-propylene-non-conjugated diene copolymer rubber, and styrene / acrylonitrile-graft-ethylene-propylene copolymer rubber. The content of rubber in the polymer alloy is preferably 50 mass % or less from the viewpoint of adding new properties to the properties of the polyolefin resin. (Based on the description in JP 2007-39592 A)
[0032] [Additives] To the composite resin composition of the present invention, other resins and additives can be added during mixing and molding, so long as the physical properties of the composition are not impaired. For example, polymerization catalysts, compatibilizers, surfactants, starches, polysaccharides, gelatin, glue, natural proteins, tannins, zeolites, ceramics, metal powders, pigments, dyes, reinforcing agents, fillers, heat resistance agents, oxidation inhibitors, weather resistance agents, lubricants, release agents, crystal nucleating agents, colorants, fragrances, leveling agents, plasticizers, flow improvers, conductive agents, antistatic agents, ultraviolet absorbing agents, ultraviolet dispersing agents, and deodorants.
[0033] The content of any additive may be appropriately determined within a range that does not impair the effects of the present invention, but is preferably about 10% by mass or less, and more preferably about 5% by mass or less, in the composite resin composition.
[0034] [Composite resin composition] The molding method using the composite resin composition of the present invention is not particularly limited, and molding methods such as injection molding, injection compression molding, extrusion molding, compression (press) molding, autoclave molding, VaRTM molding, rotational molding, blow molding, transfer molding, lamination molding, calendar molding, foam molding, vacuum molding, pressure molding, powder molding, cast molding, and hollow molding can be applied. Since the molded article using the composite resin composition of the present invention has the above-mentioned properties, it can be suitably used in the fields of, for example, office automation equipment, information and communication equipment, automobile parts, and building materials.
[0035] [Mold of reinforcing fiber] As shown in Fig. 3, the reinforcing fiber fabric 1 is a bidirectional fabric made by weaving a plurality of reinforcing fiber bundles 2, which are aligned in one direction so as to be parallel to each other, in two directions that intersect at right angles. The bidirectional fabric has the advantages that it is easily deformed into a three-dimensional shape due to changes in the relative positions of the reinforcing fiber bundles 2, and that it is easy to obtain a laminated molding material having mechanical pseudo-isotropy with a small number of sheets. The reinforcing fiber bundles 2 may be carbon fiber bundles, graphite fiber bundles, glass fiber bundles, basalt fiber bundles, aramid fiber bundles, etc., and are preferably carbon fiber bundles. By using the carbon fiber bundles, the mechanical properties of the final product, that is, the carbon fiber reinforced composite material molded product, can be improved. In light of the spirit of the present invention, the reinforcing fibers may be in the form of a fiber other than a woven fabric. The main forms of reinforcing fibers include unidirectional materials, woven fabrics, braided fabrics, knitted fabrics, non-crimp fabrics, and nonwoven fabrics.
[0036] The resin material 4 attached to the surface and inside of the reinforced fiber fabric 1 is a thermoplastic epoxy resin, which can be impregnated between the fibers of the reinforced fiber fabric to obtain the effect of bonding the layers of the reinforced fiber fabric. By making the resin material 4 mainly composed of a thermoplastic resin, the handleability is improved when the reinforced fiber fabric 1 is laminated and deformed into a three-dimensional shape and then the layers of the reinforced fiber fabric 1 are bonded together, thereby improving productivity. [Dispersion of hydrophobic nanocellulose fibers in monomer] In the present invention, a specific method for easily dispersing nanocellulose fibers uniformly in a resin is to (i) add and stir hydrophobic nanocellulose fibers to (ii) a monomer. At this time, as shown in Figure 4, the melt viscosity of the monomer is 3 to 4 orders of magnitude lower than the melt viscosity of the polymer, and hydrophobic nanocellulose fibers are easily dispersed in the monomer, so that the nanocellulose fibers are uniformly dispersed in the monomer. (iii) When the monomer is polymerized in this state in which the nanocellulose fibers are uniformly dispersed in the monomer, a nanocellulose fiber composite resin composition in which the nanocellulose fibers are uniformly dispersed is obtained. The obtained nanocellulose fibers composite resin composition It exhibits high mechanical properties, and furthermore, by using this nanocellulose fiber composite resin composition in the matrix of fiber-reinforced composite materials (FRP) such as carbon fiber, as shown in Figure 5, it is possible to improve the performance of the FRP (improved bending strength, interlaminar shear strength, impact strength, and fatigue strength). Examples of fiber-reinforced composite materials are materials obtained by impregnating reinforcing fibers with resin and compounding them, and include prepregs in which reinforcing fibers are impregnated with resin that is not fully polymerized, molded products in which reinforcing fibers are impregnated with polymerized resin, and molded products obtained by laminating and molding prepregs and polymerizing the resin. EXAMPLES
[0037] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. The components used in the examples and comparative examples are as follows. (A) Component: Nanocellulose fiber Hydrophilic nanocellulose fiber: Product name BiNFi-s BMa10010 [manufactured by Sugino Machine Co., Ltd.] Hydrophobic nanocellulose fiber: Surface hydrophobic cellulose nanofiber nanoforest-M [manufactured by Chuetsu Pulp Industry Co., Ltd.] (derived from bamboo pulp) α-cellulose content of raw material is 86%
[0038] (B) Component: Thermoplastic epoxy monomer: DENATITE XNR6850V [Nagase ChemteX Corporation] ((a) mixture of bifunctional epoxy compound and (b) bifunctional phenol compound) Catalyst: DENATITE XNH6850V [Nagase ChemteX Corporation] ((Ha) phosphorus catalyst)
[0039] The process followed is shown in Figure 6. As shown in Figure 6, we prepared sample 1, which is a hydrophilic nanocellulose fiber with a solid content of 10% made from wood pulp, and sample 2, which is a hydrophobic nanocellulose fiber with a solid content of 10% made from bamboo pulp. Samples 1 and 2 were mixed with a thermoplastic epoxy monomer at a content rate of 1.0%. After mixing, the mixture was degassed at 105°C in a vacuum dryer, and a catalyst was added.
[0040] The obtained composite resin composition was subjected to magnified observation using an electron microscope to check the dispersibility of the nanocellulose fibers. The photograph is shown in Figure 7. As shown in Figure 7, the nanocellulose fibers were better dispersed in the hydrophobic sample (sample 2) than in the hydrophilic sample (sample 1).
[0041] Samples 1 and 2 were mixed with a thermoplastic epoxy monomer in a content range of 0.5 to 2.0%, and then degassed in a vacuum dryer at 105° C., and a catalyst was added. The composite resin composition obtained above was impregnated into a carbon fiber fabric 3 shown in Fig. 3, and polymerized by heat to produce a prepreg in which polymer and monomer were mixed. Ten sheets of the resin-impregnated prepreg were laminated, and the polymerizable thermoplastic epoxy resin was polymerized by press molding and heat to produce a carbon fiber reinforced composite material molded product.
[0042] A bending test was conducted on this carbon fiber reinforced composite material using the method shown in Figure 8. The test piece used was 15 mm wide, 100 mm long, and 2 mm thick. A universal test was used for the test, with a three-point bending test performed at a support distance of 80 mm and a test speed of 5 mm / min. The results are shown in Figure 9. As shown in the figure, by mixing sample 2 with thermoplastic epoxy monomer, the bending strength of the carbon fiber reinforced composite material was improved by 11%.
[0043] Furthermore, an impact resistance test was carried out on the carbon fiber reinforced composite material obtained using Sample 2 by the method shown in Figure 10. The test piece used was 10 mm wide, 80 mm long, and 2 mm thick. The test was a Charpy impact test in which an impact was applied to the flatwise test piece with a pendulum hammer. The results are shown in Figure 11. As shown in Figure 11, by mixing Sample 2 with thermoplastic epoxy monomer, the impact strength of the carbon fiber reinforced composite material was improved by 23%. Furthermore, a short beam test was performed to measure the shear strength in the direction in which layers were shifted parallel to each other on the carbon fiber reinforced composite material obtained using sample 2 using the method shown in Figure 12. The test specimens used were 10 mm wide, 15 mm long, and 2 mm thick. The test was performed using a universal test, with a bending test of the short specimens at a support distance of 10 mm and a test speed of 2 mm / min. The results are shown in Figure 13. As shown in Figure 13, the shear strength of the carbon fiber reinforced composite material was improved by 9% by mixing nanocellulose fibers with thermoplastic epoxy monomer. [Industrial Applicability]
[0044] The present invention relates to a composite resin composition and a fiber-reinforced composite material, which have excellent environmental characteristics due to the use of biomass materials, low specific gravity and high rigidity, i.e., high specific rigidity and excellent molded appearance, good thermal stability, and flame retardancy, and a production method thereof, and therefore the composite resin composition and fiber-reinforced composite material can be suitably used in, for example, fields such as office automation equipment, information and communication equipment, automobile parts, and building materials.
Claims
1. The method for producing a fiber-reinforced composite material includes the steps of: adding 0.3% by mass to 1.0% by mass of hydrophobic nanocellulose fibers having an average thickness of 3 to 200 nm, a raw material α-cellulose content of 60% to 99% by mass, and some of the hydroxyl groups on the fiber surface substituted with hydrophobic functional groups to 99.7 to 99% by mass of a bifunctional epoxy compound and a bifunctional phenol compound that are polymerized by reaction to form a phenoxy resin; adding a catalyst to this mixture and then impregnating the reinforcing fibers; and polymerizing the bifunctional epoxy compound and the bifunctional phenol compound by heating; wherein some of the hydroxyl groups in the cellobiose units of the hydrophobic nanocellulose fibers are substituted with vinyl esters, the degree of substitution is 0.2 to 1.2, and the reinforcing fibers are carbon fibers.
2. A composite resin monomer composition comprising: 0.3% by mass to 1.0% by mass of hydrophobic nanocellulose fibers having an average thickness of 3 to 200 nm, a raw material α-cellulose content of 60% to 99% by mass, and in which some of the hydroxyl groups on the fiber surface have been substituted with hydrophobic functional groups; and 99.7 to 99% by mass of a bifunctional epoxy compound and a bifunctional phenol compound that become a phenoxy resin exhibiting thermoplasticity when polymerized by reaction, wherein some of the hydroxyl groups in the cellobiose units of the hydrophobic nanocellulose fibers have been substituted with vinyl esters, the degree of substitution being 0.2 to 1.2, and the nanocellulose fibers are uniformly dispersed in the bifunctional epoxy compound and the bifunctional phenol compound.
3. A prepreg composition comprising: hydrophobic nanocellulose fibers having an average thickness of 3 to 200 nm, a raw material α-cellulose content of 60% to 99% by mass, and 0.3% to 1.0% by mass of hydrophobic nanocellulose fibers in which some of the hydroxyl groups on the fiber surface have been substituted with hydrophobic functional groups; and 99.7 to 99% by mass of a bifunctional epoxy compound and a bifunctional phenol compound that become a phenoxy resin exhibiting thermoplasticity when polymerized by reaction, wherein some of the hydroxyl groups in the cellobiose units of the hydrophobic nanocellulose fibers have been substituted with vinyl esters and have a substitution degree of 0.2 to 1.2, and the nanocellulose fibers are uniformly dispersed in the bifunctional epoxy compound and the bifunctional phenol compound, and a carbon fiber fabric.
Citation Information
Patent Citations
Method for molding fiber-reinforced thermoplastic resin
JP2006321897A
Aromatic polycarbonate resin composition and its molding
JP2010215791A
Dispersion liquid containing cellulose nanofiber and resin, and resin composition
JP2013166818A
Method of producing hydrophilic nanofiber composite material
JP2013170241A
Resin composition
JP2014034616A